Myoglobin from the burrowing reptile Amphisbaena alba: concentrations and functional characteristics - Weber, Roy E; Johansen, Kjell; Abe, Augusto Shinya [UNESP] (Elsevier B.V., 1981)
1. 1. Myoglobin from the subterranean reptile Amphisbaena alba was isolated for measurement of concentrations and physico-chemical properties. 2. 2. The concentrations (averaging 12.1 mg.g-1 wet weight in the temporal muscles and 5.8-6.0 in the muscles that motivate the wedge-shaped head which forms the burrowing tool) far exceed those earlier reported for reptiles and other terrestrial vertebrates. 3. 3. The myoglobin has a low O2 affinity compared to mammals (P50 = 2mmHg at 25°C). In the presence of the same myoglobin O2 tension as in mammals this appears to favour similar in vivo O2 saturations at the lower reptilian body temperature. 4. 4. The temperature sensitivity of P50 reflect a heat of oxygenation, ΔH near -13 kcal· mol-1. The myoglobin is monomeric and thus lacks cooperativity in O2 binding and there is no Bohr effect. 5. 5. The pattern of microheterogeneity is similar to that of myoglobin of terrestrial vertebrates but different to aquatic mammals and reptiles. The major and two minor components exhibit very similar O2 affinities. 6. 6. The concentrations and oxygen-binding characteristics of Amphisbaena myoglobin are discussed with regard to the flow of O2 to the mitochondria during digging activity in hypoxic burrow environments. © 1981.